Implementation of MOORA Method for Food Crop Selection Based on Soil Condition - Lalu Puji Indra Kharisma; Zohriah Zohriah (Jurnal Krisnadana, 2025)
Food Crops are something that grows and has leaves, roots, stems and can be consumed by humans. Food crops are a source of life for humans, so their existence is very much needed as long as humans are still alive. Integrated food crop management efforts need to be implemented in farming activities in order to increase productivity with knowledge of the suitability of food crops and soil conditions that function as a source of information or second opinion of the Agriculture Service UPT-PP Lenek District. Therefore, a Decision Support System for selecting food crops based on soil conditions was created to facilitate the selection of the right food. The food crops used are peanuts, rice, corn, sweet potatoes. The food will be matched with criteria such as Temperature, Rainfall, soil moisture, Soil Ph, and Depth, Surface Relief. The Decision Support System method used is the MOORA method. This method has good selectivity because it can determine the objectives of conflicting criteria. Where the criteria can be profitable (benefit) or unprofitable (cost)”. The calculation stages of the MOORA method start from Creating a decision matrix, then calculating the normalization matrix, then calculating the optimization value and finally ranking. The results obtained are alternative A2, namely rice, has the highest value with a value of 0.55007.